Problemy badawcze struktury przestrzennej przemysłu - Zbigniew Zioło (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2008)
In the development of every field of science, we observe a sequence of stages connected with more and more precise perception of the research area, resulting from making new hypotheses, setting new goals, and perfecting the research methodology. These stages are reflected in the gradual transition from descriptions of the object of research and explanations of its formation processes to the creation of models and construction of theories. Thus, a need emerges to take up efforts to create the theory of industrial geography. It results not only from the willingness to intensify the elementary research, but also from social demands that use the results of scientific research in practical application, e.g. in building developmental strategies for national, regional, or local systems.